Islam dan Kaum Minoritas non-Muslim dalam Piagam Madīnah - Mary Silvita (Refleksi, 2012)
This paper would like to point out that the conception of citizenship in the doctrine of comprehensive ethics of Islam are in line with the ethics of modern democracy and human rights equation. The background of the emergence of the concept of citizenship in the classical Islamic doctrine is influenced of a war situation, namely the global terms of conflict between Islam and non-Muslims. However, the classical scholars concept of dzimmī that contain elements of discrimination is no longer can be applied because it is not in accordance with the example of the Prophet and also the concept of the modern state. So that the treatment of non-Muslim minorities must be returned by the example of the Prophet as set forth in the Charter of Medina, whose contents are still relevant to modern context for it contains universal human values.DOI: 10.15408/ref.v13i3.904